Development of Android Web KNRP.Org Applications Using Restful API And Framework Ionic (Node JS) - Permana, Angga; Sofian, Erza (I-STATEMENT, 2018)
Developing Knrp.org sites android application is based by the use of smartphones and tablets are starting to become a necessity in todays society are also with the many who visit the site knrp.org using mobile devices. Applications are made to information about KNRP (National Committee for Palestinian People) can be accessed anywhere and anytime as long as the Internet connection allows. During this time Information contained in the form of websites, social media, and print media. The purpose to develop knrp.org site to maximize KNRP publication, then in this thesis proposal created an android app that KNRP humanitarian agencies can better reach readers. Android app there are several features that can facilitate the reader KNRP in getting the best reading comfort. KNRP android app provides information about the PIC and Palestina and can be accessed in a variety of sizes of smartphones and tablets. The method application created by using Ionic Framework with a basic JavaScript Framework AngularJS, and Node.js. After going through the process of testing has been done, the application made to show information such as news-gathering KNRP and Opera-related donations.